جريمة ترك الاطفال وتعريضهم للخطر الاجتماعي في ضوء قانون حقوق الإنسان - حسين, محمد أمين (roa, 2021)
لقد أقرت اتفاقية حقوق الطفل للأمم المتحدة لعام 1989 و التي صادقت عليها الجزائر بتاريخ 19 ديسمبر 1992 بنصها في المادة الأولى على أنه "لأغراض هذه الاتفاقية يعني الطفل كل إنسان دون الثامنة عشرة  ما لم يبلغ سن الرشد قبل ذلك بموجب القانون المنطبق على الطفل ".      غير ان  الاتجاه الحديث سواء في نطاق التشريع الجزائري أو على المستوى الدولي ، يحرص على  تدعيم حماية الأطفال بتوسيع دائرتها و زيادة فعاليتها ، فالطفل ضعيف ذهنيا و بدنيا ، بصورة لا تمكنه من الدفاع أو الحفاظ على حقوقه مما يجعله أكثر عرضة من غيره ليكون ضحية للعديد من الجرائم . لذا سنتناول في هاته المداخلة الجرائم الماسة بالأطفال في قانون العقوبات الجزائية  نظرا لأهمية هذه الفئة في حياة كل المجتمعات ، و كلما تقدم المجتمع في مضمار الحضارة كلما كانت هناك ضرورة لرعاية الأطفال.     ومن بين هاته الجرائم جريمة ترك الاطفال وتعريضهم للخطر التي نصت عليها المادة37 من اتفاقية حقوق الطفل على أن لا يعرض أي طفل لضرب من ضروب المعاملة اللاانسانية ، و من هنا نجد قانون العقوبات الجزائري قد كرس هذه الحقوق ، و دعمها بحماية جنائية في القسم الثاني من الفصل الثاني من الباب الثاني من الكتاب الثالث تحت عنوان " في ترك الأطفال و العاجزين و تعريضهم للخطر "، و من المؤكد أن هذه الجريمة تؤثر في الحالة المعنوية للطفل الذي هو محور دراسة الحال و تعرض نفسيته للاضطراب و الفزع ، إلا أنها قد تؤثر على السلامة الجسدية له  إذا تعرض لاعتداء نتيجة ذلك الترك أو التخلي في مكان خالي أو غير خالي من الناس  ، و هو ما سنتطرق إليه من خلال إبراز صورتي هذا الفعل المتمثلة في تعريض الطفل للخطر ( المادة 314 من قانون العقوبات ) و هي الصورة الأولى ، و التعريض على التخلي عن الطفل ( المادة 320 من قانون العقوبات )  ومن هذا المنطلق نطرح الاشكالية التالية: ما هي أركان كل جريمة و كيف تتم متابعة مرتكبيها و توقيع الجزاء عليهم ؟ A summary of the study:       In the 1989,  United Nations Convention on the Rights of the Child, which Algeria ratified on December 19, 1992, approved its text in Article 1: For the purposes of this convention, a child means every human being under the age of eighteen, unless under the law applicable to the child, majority is attained earlier. However, the modern trend, both within the scope of Algerian legislation, or at the international level. It works to strengthen the protection of children by expanding its circle and increasing its effectiveness. The child is mentally and physically weak, in a way that does not enable him to defend or preserve his rights, which makes him more likely than others to be a victim of many crimes. In this article, we aim to know the crimes that affect children in the Criminal Penal Code, given the importance of this category in the lives of all societies. Where the more society advances in civilization, the more necessary to take care of children,  Among these crimes is the crime of abandoning children and exposing them to danger stipulated in Article 37 of the Convention on the Rights of the Child. We find the Algerian Penal Code has enshrined these rights, and support it with criminal protection in the second section of the second chapter of the second chapter of the third book entitled "On leaving children and the helpless and exposing them to danger", Certainly, this crime affects the child's moral status, which is the focus of case study, and exposes his psyche to turmoil and panic, However, it may affect his physical safety if he was assaulted as a result of that abandonment or abandonment in an empty or not empty place.This is what we will address by highlighting this act of exposing the child to danger (Article 314 of the Penal Code), which is the first one , And exposing the abandonment of the child (Article 320 of the Penal Code.